The Difference Between Giving Iron Syrup and Vitamin C with Leaflet Media Education on Hemoglobin Levels in Stunted Toddlers Aged 2–5 Years in Perdana Village, Kembang Janggut District - Asni Asni; Risnawati Risnawati; Widya Astutik (Journal of Community Health Provision, 2026)
Stunting remains a health problem in toddlers, often accompanied by low hemoglobin levels due to iron deficiency. This condition can disrupt children's growth and development, requiring effective intervention. This study aims to analyze the differences in the provision of iron syrup and vitamin C with leaflet media education on hemoglobin levels in stunted toddlers aged 2–5 years in Perdana Village, Kembang Janggut District. The study used a quantitative method with a quasi-experimental design through a pretest-posttest control group design approach. The study population was 67 stunted toddlers with a sample of 36 respondents divided into experimental and control groups using a purposive sampling technique. The research instrument used the Easy Touch GCHb hemoglobin test and observation sheets. Data analysis was performed using the Wilcoxon Signed Rank Test and Mann-Whitney test. The results showed that the average hemoglobin level in the experimental group increased from 10.256 g/dL to 11.278 g/dL with a p-value